Implementación de un software para la gestión del mantenimiento de la flota vehicular de la empresa pública Vialsur de la provincia de Loja. - Castillo León, Elton Jhon (2019)
The present research work entitled "IMPLEMENTATION OF A SOFTWARE FOR MANAGEMENT OF THE MAINTENANCE OF THE VEHICULAR FLEET OF THE PUBLIC COMPANY VIALSUR OF THE PROVINCE OF LOJA", had as general objective: To implement a software for the management of the maintenance of the vehicular fleet of the public company VIALSUR de Loja, with the purpose of automating the process of vehicle maintenance management, with which it is possible to reduce management time, improve the quality of maintenance, which will be reflected in the useful life of the vehicle. In order to achieve the general objective, different activities were carried out, including the collection of information on the entire vehicle fleet of the public company VIALSUR in the city of Loja, using techniques such as interviewing and gathering information to synthesize it. Given the nature of the software to be developed, we chose to use the MSF software development methodology, which allows us to include the client in all phases of the solution's construction, as well as to adequately document the requirements. In addition, a comparative analysis of programming and database languages was carried out, from which it was decided to build the software with Microsoft .Net Framework 4.5 using the C # programming language and SQL Server Express for its advantages over other technologies. In the case of construction of the solution, in order to achieve the stated objective, which was the construction of the software solution; finally the final work was validated and socialized with VIALSUR staff. Finally, it was possible to determine the current process of maintenance of the vehicle fleet of the company VIALSUR, the information on maintenance management was collected and the system was designed according to the needs of the same.